GC-MS Analysis of Frankincense Extracts which Inhibit the Growth of Bacterial Triggers of Selected Autoimmune Diseases - Biggs, Isaac; Sirdaarta, Joseph; White, Alan; Cock, Ian Edwin (Pharmacognosy Communications)
Introduction: Frankincense has been used traditionally for the inhibition of microbial growth and for the treatment of rheumatic diseases. Despite this, frankincense extracts are yet to be tested for the ability to inhibit the growth of the bacterial triggers of autoimmune inflammatory diseases. Methods: Solvent extracts prepared from commercially obtained frankin- cense were analysed for the ability to inhibit the growth of bacterial species associated with initiating rheumatoid arthritis (P. mirabilis), ankylosing spondylitis (K. pneumoniae) and multiple sclerosis (A. baylyi, P. aeruginosa) by disc diffusion assay, and quantified by MIC determination. Toxicity was determined by Artemia franciscana bioassay.The most potent inhibitory extracts were investigated using non-targeted GC-MS head space analysis (with screening against a compound database) for the identification and characterisation of individual components in the crude plant extracts. Results: Methanolic and aqueous frankincense extracts inhibited the growth of all bacterial species. The growth inhibition of these extracts was particularly notable against P. mirabilis and K. pneumoniae, with MIC values generally ≤ 1000 µg/mL for both reference and clinical bacterial strains. Indeed, the MIC values of the methanolic extract against P. mirabilis, and for the aqueous extract against K. pneumonia, were as low as 59.6 and 75.2 µg/mL respectively. The methanolic and aqueous extracts also inhibited the growth of A. baylyi and P. aeruginosa. However, with the exception of the growth inhibition of A. baylyi by the aqueous extract (MIC=4313 µg/mL: moderate inhibitory activity), the MICs against these bacteria was indica- tive of only low inhibitory activity. The ethyl acetate, chloroform and hexane extracts also inhibited the growth of all bacterial species, albeit with low efficacy (MIC values generally >5000 µg/mL against all bacterial species). All frankincense extracts were non-toxic in the Artemia franciscana bioassay, with LC50 values substantially above 1000 µg/mL. Non-biased GC-MS head- space analysis of the methanolic and aqueous extracts putatively identified a high diversity of monoterpenoids and sesquiteriterpenoids. Conclusion: The lack of toxicity and the inhibitory activity of the methanolic and aqueous frankincense extracts against microbial triggers of rheumatoid arthritis and ankylosing spondylitis indicates their potential in the treatment and prevention of these diseases.
Keywords: Boswellia; Terpenoid; Monoterpene; Sesquitertene; Rheumatoid Arthritis; Ankylosing spondylitis; Multiple sclerosis